The Potrayal of Peace Values Embedded in the Indonesian ELT Textbook as a Site of Character Education for Secondary High School Students - Dimas Arif (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Abstract  This study examined what peace values are represented in English textbook for Tenth-Grade Senior High School students published by the Ministry of Education and Culture of the Republic of Indonesia by using visual semiotics of Roland Barthes. The study explored visual images about peace values in English textbook for tenth-grade Senior High School students to be analyzed by using of Roland Barthes’s theory of visual semiotics which develop two aspects in visual semiotics’ meaning-making: denotation and connotation are to expose the image representation in the form of ideas and values within it. The findings show that there are three categories of peace values represented in the English. The most represented peace values can be found in the target textbook is social peace. On the other hand, peace with nature were seriously under-represented through images in the target textbook. Therefore, an innovative way from English teachers in delivering vary teaching and learning activities related to the images given in the textbook is absolutely essential for the students implement character building proposed by ministry of education in their daily lives.